The Effect of Soaking Temperature on the Kinetic Model of Rehydration of Dried Oyster Mushrooms (Pleurotus ostreatus) - Maharani, Dewi Maya; Muhammady, Iqbal Harzulmi; Ubaidillah, Ubaidillah; Hawa, La Choviya (Graduate School, Universitas Brawijaya, 2026)
Oyster mushrooms (Pleurotus ostreatus) pack a powerful nutritional punch. However, they spoil easily and require special handling for dehydration. Temperature during rehydration is a key factor affecting the quality recovery of mushrooms. Yet, there are limited studies on rehydration kinetics at different temperatures. The principal objective of this study was to investigate how soaking temperatures (25±1°C, 40±1°C, 50±1°C, 60±1°C, and 70±1°C) affect rehydration ratio, moisture content, water absorption rate, and volume expansion ratio at 120 minutes, with three repetitions. The results showed that physical recovery was dominant at lower temperatures (25–40°C). Maximum moisture content (0.850 g.g-1) was achieved at 40°C. In contrast, the optimal rehydration ratio (6.549) occurred at 25 °C. High temperatures (60–70°C) increased the kinetic rate of water absorption, reaching a peak at 60±(0.081g.g-1 min). Volume expansion reached its maximum at 70 °C (1.482). Based on mathematical modeling results, the Midilli-Kucuk model had the highest predictive accuracy at 25°C and 60°C. The Two-Term model captured rehydration phenomena better at 50°C and 70°C. The Bidkhori-Karizaki model provided the most precise data fit when applied at 48°C. Using high temperatures, such as 70°C, can significantly accelerate rehydration kinetics. However, there are technical consequences, including high total energy consumption and risk of structural damage to the product. These effects can reduce its final quality, which is critical for industrial-scale implementation. Therefore, to balance efficiency and product quality, a soaking temperature range of 25–40 °C is recommended as the most optimal operational condition.